Ascites and other incidental findings revealing undiagnosed systemic rheumatoid arthritis. (8th June 2015) - Szeto, Matthew Chak Hin; Disney, Benjamin; Perkins, Philip; Wood, Gordon
Abstract : We describe a case of a 43-year-old man presenting to the gastroenterology outpatient department with exudative ascites. Mediastinal lymphadenopathy, pericardial effusion and pleural effusion were detected on further imaging. Further clinical examination revealed subcutaneous nodules on the left arm, which were confirmed to be rheumatoid nodules on histology. Inflammatory markers were elevated with positive serology for rheumatoid factor and anticyclic citrullinated protein antibody. Our investigations excluded tuberculosis, pancreatitis and malignancy in the patient. Following review by a rheumatologist, a diagnosis of systemic rheumatoid arthritis (RA) was made. Pleuritis and pericarditis are well recognised as extra-articular manifestation of RA. Ascites, however, is rarely recognised as a manifestation of RA. Our literature search revealed two other cases of ascites due to RA disease activity, and both patients had long-standing known RA. This case adds to the discussion on whether ascites and peritonitis should be classified as extra-articular manifestations of RA.